2011
DOI: 10.1103/physrevb.83.195321
|View full text |Cite
|
Sign up to set email alerts
|

Material configurations forn-type silicon-based terahertz quantum cascade lasers

Abstract: Silicon-based quantum cascade lasers (QCLs) offer the prospect of integrating coherent THz radiation sources with silicon microelectronics. Theoretical studies have proposed a variety of n-type SiGe-based heterostructures as design candidates, however the optimal material configuration remains unclear. In this work, an optimization algorithm is used to design equivalent THz QCLs in three recently-proposed configurations [(001) Ge/GeSi, (001) Si/SiGe and (111) Si/SiGe], with emission frequencies of 3 and 4 THz.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 62 publications
0
36
1
Order By: Relevance
“…This requires the manual selection of the injector state prior to simulating the device, and omits tunneling through the injection barrier from other states. This approach is not well-suited to semi-automated design procedures, 6,28 and can be problematic in bound-tocontinuum (BTC) designs, in which multiple states may contribute to the tunneling current. Furthermore, these simplified models neglect coherences between the injector state and other states in the same period.…”
Section: -11mentioning
confidence: 99%
See 3 more Smart Citations
“…This requires the manual selection of the injector state prior to simulating the device, and omits tunneling through the injection barrier from other states. This approach is not well-suited to semi-automated design procedures, 6,28 and can be problematic in bound-tocontinuum (BTC) designs, in which multiple states may contribute to the tunneling current. Furthermore, these simplified models neglect coherences between the injector state and other states in the same period.…”
Section: -11mentioning
confidence: 99%
“…Several theoretical studies of Si-based QCLs exist, [6][7][8][10][11][12][13] but none have accounted for coherent transport effects (i.e., quantum tunneling and interactions with optical fields). Although semiclassical scattering-transport models can give good agreement with experimental results, 1,14 they neglect tunneling across barriers, and can predict unrealistically large spikes in current density and gain when electrons scatter between spatially-extended subbands.…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon is the only material that allows mature processing technology which may reduce costs and allow integration with conventional electronic devices. A recent report on silicon based QCL focused on a variety of n-type SiGe-based heterostructures as design candidates [Valavanis et al, 2011]. They have carried out theoretical studies on (001) Ge/GeSi, (111) Si/SiGe, and (001) Si/SiGe material configurations where they have found that (001) Ge/GeSi is the most promising system for development of a Si-based QCL…”
Section: Quantum Cascade Laser Emittersmentioning
confidence: 99%